PEMBUATAN ALAT PERMAINAN EDUKATIF (APE) ROBOT PINTAR DENGAN MENGGUNAKAN BARANG BEKAS UNTUK ANAK USIA 4-5 TAHUN - Auliyatun Najah; Hana Shofia; Auli Nuril Arifah; Luthfatun Nisa’ (Al-Abyadh, 2023)
Existence is a key in carrying out a lesson, in this case the lack of creativity of educators in making learning media is still an obstacle to providing educational game tools in the teaching and learning process. In increasing creativity between educators and parents of students, namely with this educational game tool. Training to process used goods is carried out to support the use of assistive devices. With the help of training on the benefits of using used goods, the aim is to be able to process goods around us and become teaching tools for children, educators, and parents of students. The utilization of unused goods is processed into goods that can be used and certainly useful. Early age is the most crucial period for stimulating brain development through learning with various toys. Educational toys as learning tools mean that toys have been produced and used in order to provide comfort in playing activities.